Comunicación intercultural y su influencia en la identidad afro ecuatoriana en el cantón San Lorenzo, período julio- diciembre 2024 - Aguilar Heras, Odalys Maylin (2025)
This study analyzed intercultural communication and its influence on the Afro-Ecuadorian identity in the canton of San Lorenzo. The main objective was to determine the level of influence of intercultural communication on the preservation and strengthening of this cultural identity. The research followed a mixed approach, through interviews with local authorities, historians, and community representatives, as well as surveys applied to the population. The results showed that Afro-Ecuadorian identity has continued to evolve, is valued in public spaces of the canton, and represents a key element for new generations. In conclusion, it was determined that intercultural communication significantly influences the transmission and strengthening of Afro-Ecuadorian identity in San Lorenzo.